ALMA CO observations of a giant molecular cloud in M 33: Evidence for high-mass star formation triggered by cloud–cloud collisions. (12th June 2020) - Sano, Hidetoshi; Tsuge, Kisetsu; Tokuda, Kazuki; Muraoka, Kazuyuki; Tachihara, Kengo; Yamane, Yumiko; Kohno, Mikito; Fujita, Shinji; Enokiya, Rei; Rowell, Gavin; Maxted, Nigel; Filipović, Miroslav D; et al.
Abstract: We report the first evidence for high-mass star formation triggered by collisions of molecular clouds in M 33. Using the Atacama Large Millimeter/submillimeter Array, we spatially resolved filamentary structures of giant molecular cloud 37 in M 33 using 12 CO( J = 2–1), 13 CO( J = 2–1), and C 18 O( J = 2–1) line emission at a spatial resolution of ∼2 pc. There are two individual molecular clouds with a systematic velocity difference of ∼6 km s −1 . Three continuum sources representing up to ∼10 high-mass stars with spectral types of B0V–O7.5V are embedded within the densest parts of molecular clouds bright in the C 18 O( J = 2–1) line emission. The two molecular clouds show a complementary spatial distribution with a spatial displacement of ∼6.2 pc, and show a V-shaped structure in the position–velocity diagram. These observational features traced by CO and its isotopes are consistent with those in high-mass star-forming regions created by cloud–cloud collisions in the Galactic and Magellanic Cloud H ii regions. Our new finding in M 33 indicates that cloud–cloud collision is a promising process for triggering high-mass star formation in the Local Group.